2018
DOI: 10.3889/oamjms.2018.311
|View full text |Cite
|
Sign up to set email alerts
|

Male Infertility and Sperm DNA Fragmentation

Abstract: BACKGROUND:One of the main factors affecting male infertility is DNA fragmentation in sperm. Male infertility is a heterogeneous group of disorders, known causes account for only 30-50%, and unknown cause (idiopathic) constitute the rest. Infertility involves nearly 15% of couples in the reproductive age, and only the male problem involves about 40% of the problems.AIM:We have studied our DNA damage to sperm cells of a group of infertile males (113 patients) with abnormal sperm parameters (oligoasthenospermia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
(17 reference statements)
1
16
0
4
Order By: Relevance
“…Refaat (2016) revealed that the Y-STR profiles of the azoospermic sperms were fully documented without any abnormalities. However, DNA fragmentation was characteristic for the infertile sperms and might be diagnostic for male infertility (Zeqiraj et al, 2018). There is no evidence that the DNA fragmentation in the infertile males could affect the STR profiling or the mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Refaat (2016) revealed that the Y-STR profiles of the azoospermic sperms were fully documented without any abnormalities. However, DNA fragmentation was characteristic for the infertile sperms and might be diagnostic for male infertility (Zeqiraj et al, 2018). There is no evidence that the DNA fragmentation in the infertile males could affect the STR profiling or the mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…The SCD assay has also been used for a long time (Fernández et al, ), being further developed under time to attempt becoming an economical and management alternative to SCSA (Feijó & Esteves, ). As such, it has been adopted by many IVF clinics since it is simple, quick, does not require expensive or complicated instruments and, moreover, has high reproducibility (<3% intra‐assay variation; Panner Selvam & Agarwal, ; Zeqiraj et al, ). The CV for the reference sample and replicates assayed in the present study were well within these values, confirming previous studies (Erenpreiss, Bungum, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the most popular for screening purposes is the sperm chromatin structure assay (SCSA), a 30‐year‐old flow cytometry/specific software‐linked methodology with high repeatability and low variation (1%–3%; Evenson, ), but requires specialised technicians for running it. Another technique with increasing popularity is the commercially available new kit for the sperm chromatin dispersion testing (SCD, HaloSpermG2 ® ; Zeqiraj et al, ). The SCD has high reproducibility (<3%) and does not require complex instruments becoming simpler and quick to run (Fernández et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its highly complex structure, sperm DNA is susceptible to damage and nearly 80% of infertility cases due to idiopathic reasons are related to DNA integrity (11). The proportion of spermatozoa with DNA fragmentation was 34.5% in infertile men while it was only 14.9% in fertile men (76). Assessment of sperm DNA fragmentation represents a promising tool for clinical and research practice (77), although larger prospective trials are needed.…”
Section: Why Test Sperm Dna Damage-consequences Of Sperm Dna Fragmentmentioning
confidence: 99%